Investigation of the phase composition of micro-arc oxidation coatings on an aluminium alloy formed in an alkaline-silicate electrolyte - Kalinichenko, Ihor (National Technical University "Kharkiv Polytechnic Institute", 2025)
The article presents the results of studying the phase composition of coatings on aluminium alloy obtained by microarc oxidation (MAO) in alkaline-silicate electrolyte in the cathodic-anodic mode. The dependence of the phase composition of the coatings on the parameters of the oxidation process, in particular, current density, processing time, and electrolyte composition, was determined. It was found by X-ray tensometry that the coatings consist mainly of α-Al₂O₃, γ-Al₂O₃ and mullite (3Al2O3⋅2SiO2) phases. The obtained results make it possible to optimise the technological modes of forming micro-arc oxidation coatings to increase their wear resistance and corrosion resistance.
Keywords: microarc oxidation; aluminium alloy; phase composition; alkaline-silicate electrolyte; X-ray tensile testing; coating thickness; hardness